Fulfillment of the Mandailing community suffrage right in the 2020 regional head election - Neva, Chandra Fhutu; Gunawati, Dewi; Triyanto, Triyanto (Universitas Negeri Yogyakarta, 2022)
Modern society presents a problem where it is increasingly common for minority groups/cultural groups/indigenous groups to show their identity to fulfill their collective right to vote in politics. This study aims to describe the form of democracy that is still hampered because the fulfillment of the voting rights of the Mandailing community is still limited. This research is qualitative descriptive research conducted in the Mandailing community in Kecamataan Sungai Kanan. Data was collected through interviews, observation, and documentation. The collected data is then analyzed using Creswell's techniques which consist of organizing and preparing the data, reading the data, the coding process or general analysis, the coding categorization process that has been made, and describing the themes into qualitative explanations and analysis. The results of this study prove that the level of understanding of the Mandailing community on the importance of the right to vote is still shallow; this is related because the KPU, as the organizer, does not seriously socialize the political rights of citizens. In this case, the right to vote and be elected. Meanwhile, monotonous activities are always represented by the Mandailing community by representing their voting rights to traditional leaders or elders in the area.